Preparation method and application of spirofluorene xanthene-based Grignarene fluorescent material

By synthesizing spirofluorene oxanthracene-fluorophenylglycolene fluorescent materials and using solution processing method, the shortcomings of the evaporation method in the existing OLED preparation methods are solved, and the effect of improving the brightness and efficiency of OLED devices is achieved.

CN119490509AActive Publication Date: 2025-02-21NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411565217.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-21
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

In the existing OLED preparation methods, the evaporation method has problems such as harsh conditions, low raw material utilization rate and severe dependence on imported equipment, which leads to the urgent need to develop solution method for preparing OLEDs.

Method used

The C-H bond activation strategy was used to synthesize the fluorescent materials of spirofluorene oxide-fluorophenyl galvanic aromatics, and the OLED devices were prepared by solution processing method to explore the influence of the lattice pore effect on the material performance.

Benefits of technology

The brightness and efficiency of OLED devices have been improved, and the current efficiency and power efficiency of devices have been effectively improved through the grid strategy, providing important reference and guidance for the further development of organic luminescent materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490509A_ABST
    Figure CN119490509A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a spirofluorene xanthene-based grignarene fluorescent material. [spirofluorene xanthene-fluorobenzene]-based grignarene (G-DSFX) is synthesized by adopting a C-H bond activation gridding method. The optimal reaction conditions are as follows: the catalyst is palladium acetate Pd (OAc), the ligand is tri-tert-butylphosphine tetrafluoroborate PtBu2Me-HBF4, the alkali is potassium carbonate K2CO3, the solvent is N, N-dimethylacetamide DMAc, the temperature is 120 DEG C, the reaction is performed for 48 hours, the reaction concentration is 20 mmol. L <-1 >, and the yield is as high as 19%. The OLED is prepared by adopting a solution processing method, I-shape, U-shape, m-shape and G-DSFX are used as OLED light-emitting layers for device testing by utilizing the solution processing method, and turn-on voltages are 3.9 V, 6.9 V, 4.5 V and 6.4 V respectively; the maximum brightness is 67.9 cd.m <-2 >, 56.69 cd.m <-2 >, 45.43 cd.m <-2 > and 72.2 cd.m <-2 > respectively; the maximum external quantum efficiency EQEmax is 0.08%, 0.06%, 0.03% and 0.15%, which proves that the lattice strategy can also improve the brightness and the external quantum efficiency of the device, and provides a reference for preparing an OLED by a solution processing method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic electroluminescent devices, and in particular relates to a preparation method and application of a spirofluorene-oxanthene-based lattice aromatic hydrocarbon fluorescent material. Background Art

[0002] So far, spirofluorene organic semiconductors have shown great potential in the field of organic optoelectronics. In the process of commercialization of organic devices, there are problems such as expensive raw materials and cumbersome preparation. Green organic semiconductors are an important solution. In 2006, we proposed the "one-pot method of spirofluorene anthracene (SFX)", which overcomes the problems of lengthy routes and expensive raw materials in the preparation of spiroaromatic hydrocarbons. At the same time, it can improve the quantum efficiency of light-emitting devices, enhance the thermal stability and photoelectric stability of materials, have strong molecular modifiability, and can also achieve industrial production. With these advantages, SFX has been widely used in the field of organic optoelectronics.

[0003] After continuous exploration, a variety of SFX derivative materials have been developed. Among them, two spirofluorene oxygen anthracene units are fused together to form spirofluorene oxygen anthracene (DSFX). The positions of the two spiro rings are fixed by the rigid skeleton of oxygen anthracene, and the distance between the two is close, which is expected to achieve high luminescence efficiency and high electron transport. In 2019, we successfully synthesized spirofluorene oxygen anthracene lattice (GS-SFX) using DSFX as the core building unit, and verified through theoretical calculations that its electronic properties and reorganization energy have reached good indicators of hole transport materials. In 2023, we developed a flexible deep blue light material based on DSFX, namely polyoxyanthracene spirofluorene, which provides an effective strategy for the development of flexible light-emitting displays. These studies fully affirm the role of DSFX in regulating the optoelectronic properties of materials.

[0004] At present, commercial OLED (organic light-emitting diode) is prepared by evaporation, but the conditions in the evaporation process are demanding, the utilization rate of raw materials is only 30%, and the evaporation machine is heavily dependent on imports, so the development of solution method to prepare OLED is the general trend. Based on this, the present invention will use the CH bond activation strategy to synthesize [spirofluorene xanthene-fluorophenyl]-based lattice aromatics, and characterize its photoelectric properties, and apply it to OLED (organic light-emitting diode) prepared by solution processing. Summary of the invention

[0005] In view of the above analysis, the purpose of the present invention is to synthesize a new type of spirofluorene xanthracene-based lattice aromatic fluorescent material, explore the influence of the lattice effect on the material performance, characterize the photoelectric properties of the material and explore the application of the material in the preparation of OLED devices, further verify that the lattice strategy can effectively improve the brightness and efficiency of the device, and provide important reference and guidance for the further development of organic light-emitting materials. The present invention is achieved by the following technical means:

[0006] The present invention first provides a spirofluorene xanthracene-based lattice aromatic fluorescent material, the structural formula of the fluorescent material is as follows: in: It is a type of spirofluorene compound;

[0007] Select any one of the following structures:

[0008]

[0009] Select any one of the following structures:

[0010]

[0011] Wherein X is any one of F, Cl, Br, I, CH3, NO2, and CH3O.

[0012] Furthermore, R on the alkyl chain is a straight chain type, including: a hydrogen atom, an alkane chain, an alkoxy chain, and an alkyl chain with a halogen atom of fluorine, chlorine or bromine introduced at the end, and the specific structure is as follows:

[0013] -H -C n H 2n+1 -OC n H 2n+1 -C n H 2n+1 F -C n H 2n+1 CI-C n H 2n+1 Br.

[0014] Furthermore, the spirofluorene compound The specific structural formula is as follows:

[0015]

[0016] The present invention also discloses a method for preparing a spirofluorene xanthracene-based lattice aromatic fluorescent material, which is synthesized by a CH bond activation lattice method, and specifically comprises the following steps:

[0017] At a reaction temperature of 80-150°C, U-shape synthon U-shape, dibromospirofluorene oxygen anthracene DBrDSFX base, ligand, organic solvent and palladium catalyst are added to react for 36-72 hours. The reaction concentration of the reaction system is 20 mmol·L-1, and the molar ratio of U-shape synthon U-shape and dibromospirofluorene oxygen anthracene DBrDSFX is 1:1, and finally a dibromospirofluorene oxygen anthracene-based lattice aromatic hydrocarbon fluorescent material is obtained.

[0018] Further, the base is selected from: potassium carbonate, potassium hydroxide, sodium carbonate, sodium bicarbonate, or a combination of two thereof;

[0019] The ligand is selected from: PtBu2Me-HBF4, phosphoramidite ligands, 1,1′-binaphthyl-2,2′-bis(diphenylphosphine) (BINAP), JosiPhos, or a combination of two thereof;

[0020] Furthermore, the organic solvent is selected from: N,N-dimethylformamide, dimethyl sulfoxide, toluene, acetonitrile, or a combination of two thereof.

[0021] Furthermore, the palladium catalyst is selected from the group consisting of: tetrakis(triphenylphosphine)palladium, palladium acetate, palladium pivalate, palladium trifluoroacetate, diphenylphosphinocenepalladium dichloride, dichlorobistriphenylphosphine palladium or palladium on carbon or a combination of one or more thereof.

[0022] Furthermore, the palladium catalyst is palladium acetate.

[0023] Furthermore, the amount of palladium acetate used is determined according to the reaction activity of different substrates, and the amount of palladium acetate substance is 0.025 to 0.05 times that of the synthon.

[0024] Furthermore, the reaction temperature is 120° C. and the reaction time is 48 h.

[0025] The invention also discloses a spirofluorene xanthracene-based lattice aromatic hydrocarbon fluorescent material prepared according to any one of the above preparation methods.

[0026] The invention also discloses an application of the spirofluorene xanthracene-based lattice aromatic hydrocarbon fluorescent material in an electroluminescent device.

[0027] Furthermore, the electroluminescent device is an organic light emitting diode.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention focuses on the synthesis, properties and applications of [spirofluorene oxygen anthracene-fluorophenyl]-based lattice aromatics. First, we confirmed through retrosynthetic analysis that the step-by-step method is also applicable to [spirofluorene oxygen anthracene-fluorophenyl]-based lattice aromatics. In addition, we screened out the optimal reaction conditions for lattice aromatics G-DSFX: reaction temperature of 120°C, reaction time of 48h, palladium acetate as catalyst, and the amount of substance of 0.025 to 0.05 times that of the synthon. PtBu2Me-HBF4 is used as a ligand, K2CO3 as a base, and the organic solvent is selected from one or a combination of two of N,N-dimethylformamide, dimethyl sulfoxide, toluene, and acetonitrile, and the reaction concentration is 20mmol·L -1 , the yield can reach up to 19%.

[0030] 2. To explore the influence of the lattice effect on the material properties, the photoelectric properties of the material were characterized. The spectral results showed ( Figure 2 ), in the solution state, compared with the linear molecule m-shape, the maximum absorption wavelength of the lattice G-DSFX is blue-shifted by 11nm, and the maximum emission wavelength is blue-shifted by 3nm; in the film state, the maximum absorption wavelength of the lattice G-DSFX is blue-shifted by 13nm, and the maximum emission wavelength is blue-shifted by 14nm. In addition, in the solution state, the PLQY of G-DSFX is significantly improved compared with that of m-shape. In the film state, the PLQY of G-DSFX is greatly reduced. It can be seen that in [spirofluorene oxygen heteroanthene-fluorophenyl]-based lattice aromatics, the aggregation quenching of molecules is more serious, resulting in a decrease in the luminescence efficiency of G-DSFX. In addition, the electrochemical test results show that the band gaps of m-shape and G-DSFX are 4.11eV and 3.88eV, respectively, and the molecular band gap is slightly reduced after latticeization.

[0031] 3. Use them as OLED light-emitting layers for application research. Test results show that ( Figure 4 ), the turn-on voltages of the linear molecule m-shape and the lattice G-DSFX are both low, 2.5V and 6.4V respectively. The maximum brightness of G-DSFX is about 1.5 times that of m-shape. In addition, the current efficiency of G-DSFX is 4 times higher than that of m-shape, and the power efficiency is 8 times higher than that of m-shape. max 5 times higher than m-shape ( Figure 5 ). These findings further verify that the grid strategy can effectively improve the brightness and efficiency of the device, providing important reference and guidance for the further development of organic light-emitting materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Figure 1 shows the structural confirmation of G-DSFX, where (a) shows the mass spectrum of DBrDSFX; (b) shows the mass spectrum of U-shape; (c) shows the mass spectrum of G-DSFX; (d) shows the mass spectrum of substrate DBrDSFX, U-shape and lattice G-DSFX. 1 H NMR superposition spectrum.

[0033] Figure 2Figure 2 is the photophysical characterization of G-DSFX, where (a) is the spectra of I-shape, U-shape, m-shape and G-DSFX in solution; (b) is the spectra of I-shape, U-shape, m-shape and G-DSFX in thin film; (c) is the fluorescence lifetime of I-shape, U-shape, m-shape and G-DSFX in different states; (d) is the photoluminescence quantum yield of I-shape, U-shape, m-shape and G-DSFX in solution and thin film.

[0034] Figure 3 CV diagrams of I-shape, U-shape, m-shape and G-DSFX; (a) is the electrochemical oxidation and reduction performance diagram of I-shape, U-shape, m-shape and G-DSFX; (b) is the energy level diagram of I-shape, U-shape, m-shape and G-DSFX.

[0035] Figure 4 The current density / brightness / voltage relationship diagram of OLED prepared by G-DSFX, where 4a: JVL curve and efficiency curve of I-shape; 4b: relationship between CE and PE of I-shape and current density; 4c: JVL curve and efficiency curve of U-shape; 4d: relationship between CE and PE of U-shape and current density; 4e: JVL curve and efficiency curve of m-shape: 4f: relationship between CE and PE of m-shape and current density; 4g: JVL curve and efficiency curve of G-DSFX; 4h: relationship between CE and PE of G-DSFX and current density.

[0036] Figure 5 (a) shows the EL spectra of I-shape, U-shape, m-shape and G-DSFX devices, (b) shows the EQE of I-shape, U-shape and m-shape devices; (c) shows the EQE of G-DSFX device.

[0037] Figure 6 This is the structural diagram of the OLED device of G-DSFX.

[0038] Figure 7 This is the synthetic route of U-shape.

[0039] Figure 8 This is the synthetic route of G-DSFX. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention and the accompanying drawings are further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0042] Example 1

[0043] Dibromospirofluorene xanthene DBrDSFX

[0044] The structural formula of the product is as follows:

[0045]

[0046] All instruments required for the reaction process, including the three-necked reaction bottle, magnet and condenser, were cleaned in advance, put into the oven to dry and set aside. First, the reaction bottle and condenser were connected and fixed, sealed with a rubber stopper, and the device was wrapped with tin foil to ensure light-proof conditions. Then the connection was completely sealed with a sealing film, leaving one bottle mouth unsealed. Then, the solid drugs 2-bromo-9-fluorenone (2.580g, 1equiv), resorcinol (1.650g, 1.5equiv) and toluenesulfonic acid (5.660g, 5equiv) were accurately weighed and put into the reaction bottle. After all the drugs were added, the last bottle mouth was sealed with a rubber stopper and a sealing film. Then the reaction device was vacuumed and nitrogen-filled, repeated three times, and a nitrogen balloon was tied for protection. Then, toluene solvent (60ml) was drawn into the reaction bottle with a syringe, and the pinhole needed to be blocked with vacuum silicone grease to prevent leakage of the device. Finally, the device was transferred to an oil bath, the temperature was set to 120℃, and condensed and refluxed for 24h. Use TLC plate to detect the reaction situation, and turn off the heating function of the oil bath pot after observing that the reaction is complete. After the reaction is cooled to room temperature, weigh K2CO3 (8.280g, 2equiv) and 1-bromooctane (5.160g, 3equiv) and add them to the reaction bottle, and seal the device again. Then turn on the heating function of the oil bath pot, set the temperature to 120℃, and end the reaction after condensation and reflux for 24h. After the reaction is cooled to room temperature, use a rotary evaporator to remove the toluene in the reaction solution. Then use dichloromethane to extract multiple times, use a rotary evaporator to mix the sample, and use a 100-200 mesh silica gel powder to load a 30cm high chromatography column for separation and purification. Use [petroleum ether: dichloromethane = 10:1] eluent to elute to obtain a white solid product, and then use dichloromethane / methanol mixed solvent to recrystallize and purify again, with a yield of 4%. 1HNMR (400MHz, CDCl3): δ7.48(d,J=7.7Hz,2H), 7.38(d,J=8.1Hz,2H), 7.32(d,J=1.7Hz,1H), 7.30(d,J=1.8Hz,1H), 7.18(td,J=7.5 ,1.1Hz,2H), 7.07(d,J=1.7Hz,2H), 7.05(s,1H), 7.02(t,J=8.0Hz,1H), 6.88(d,J=7.6Hz,2H), 6.74(d,J=2.5Hz,2H), 5.32(s,1H); 13 C NMR (101MHz, CDCl3) δ159.1,155.9,153.4,152.2,151.2,138.2,137.7,130.6,128.1,127.9,127.4, 126.6,125.1,121.4,120.8,120.5,119.4,115.9,111.0,104.3,101.8,77.2,76.8,76.5,68.0,53.5.

[0047] Example 2

[0048] U-shaped synthonU-shape

[0049] The structural formula of the product is as follows:

[0050]

[0051] All instruments needed for the reaction, including Schlenk reaction flasks and magnets, were cleaned in advance and placed in an oven for drying. First, the reaction flask was fixed on an iron stand and wrapped with tin foil to ensure light protection. Then, solid drugs DBrDSFX (0.200 g, 1 equiv), K2CO3 (0.055 g, 2 equiv), P tBu2Me-HBF4 (0.010g, 0.2equiv) and Pd(OAc)2 (0.045g, 0.1equiv), then use a syringe to draw 1,2,4,5-tetrafluorobenzene (0.600g, 20equiv) and solvent DMAc (2.5ml) into the reaction tube. After all are added, the reaction device is evacuated and nitrogen-filled. Repeat three times and tighten the stopper under nitrogen. Finally, the device is transferred to an oil bath pot, the temperature is set to 110°C, and the reaction is terminated after condensation and reflux for 48h. After the reaction is cooled to room temperature, ethyl acetate / water is used for multiple extractions to remove the high-boiling solvent DMAc. The sample was then mixed using a rotary evaporator, and separated and purified using a 25 cm high chromatography column loaded with 200-300 mesh silica gel powder, and eluted using an eluent with a polarity of [petroleum ether: dichloromethane = 8:1] to obtain a white solid product, which could be purified again by recrystallization using a dichloromethane / n-hexane mixed solvent, with a yield of 84%. 1 H NMR (400MHz, CDCl3) δ7.64(d,J=7.9Hz,2H), 7.55(d,J=7.5Hz,2H), 7.18(t,J=7.4Hz,2H), 7.07–6.95( m,8H), 6.85(q,J=8.3Hz,2H), 6.72(s,2H), 6.32(d,J=8.5Hz,2H), 6.21(d,J=8.8Hz,2H), 5.46(s,1H); 13 C NMR (101MHz, CDCl3) δ159.6,155.7,154.3,152.7,151.7,141.4,138.1,130.0,129.1,128.6,127.9,127.7,127.2,126.9,125.5,121.9 ,121.8,121.7,121.1,120.5,120.0,116.8,111.6,107.7,104.8,104.6,104.3,103.8,102.3,77.8,77.8,77.5,77.2,76.8,76.6,68.6.

[0052] Example 3

[0053] [Spirofluorene-oxanthene-fluorophenyl]-based lattice arene G-DSFX

[0054] The structural formula of the product is as follows:

[0055]

[0056] All instruments needed for the reaction, including Schlenk reaction bottles and magnets, were cleaned in advance and placed in an oven for drying. First, the reaction bottle was fixed on an iron stand and the device was wrapped with tin foil to ensure light protection. Then, the solid drugs U-shape (0.262 g, 1 equiv), DBrDSFX (0.200 g, 1 equiv), K2CO3 (0.055 g, 2 equiv), P t Bu2Me-HBF4 (0.010g, 0.2equiv) and Pd(OAc)2 (0.045g, 0.1equiv), and the solvent DMAc (6ml) was drawn with a syringe. After all the drugs and solvents were added to the reaction tube, the reaction device was evacuated and nitrogen-filled, and the process was repeated three times. The stopper was tightened under nitrogen. Finally, the device was transferred to an oil bath, the temperature was set to 120°C, and condensed and refluxed for 48h. The reaction was terminated. After the reaction was cooled to room temperature, ethyl acetate / water was used for multiple extractions to remove the high-boiling solvent DMAc. The sample was mixed using a rotary evaporator, and a 25cm high chromatography column loaded with 200-300 mesh silica gel powder was used for separation and purification. The eluent with a polarity of [petroleum ether: dichloromethane: acetone = 60:6:1] was used for elution to obtain a white solid product, which can be purified again by recrystallization with a dichloromethane / n-hexane mixed solvent, with a yield of 19%. 1 H NMR(400MHz, CDCl3) δ7.70(d,J=8.0Hz,4H), 7.57(d,J=7.6Hz,4H), 7.19–6.95(m,22H), 6.71(d,J=2.5Hz,4H), 6.28(dd,J=8.7,2.6Hz,4H), 6.17(d,J=8.7Hz,4H), 5.63(s,1H); 13 C NMR (101MHz, CDCl3) δ157.9,157.3,150.9,150.4,144.7,143.9,143.4,141.0,140.3,140.2, 140.2,138.8,137.3,136.0,135.8,133.5,130.6,130.4,129.9,129.4,128.0,127.6,127.3,1 27.1,126.8,126.5,126.5,126.1,125.9,125.9,125.5,125.3,125.1,124.9,124.7,123.9,1224,119.4,119.2,113.1,109.9,100.6,91.7,82.4,76.2,76.0,75.8,75.5,70.1,66.9,66.8.

[0057] Example 4

[0058] Type I synthonI-shape

[0059] The structural formula of the product is as follows:

[0060]

[0061] All instruments needed for the reaction, including Schlenk reaction flasks and magnets, were cleaned in advance and placed in an oven for drying. First, the reaction flask was fixed on an iron stand and the device was wrapped with tin foil to ensure light protection. Then, the solid drug 2-bromospirofluorene xanthene 2-BrSFX (0.198 g, 3 equiv), K2CO3 (0.048 g, 2 equiv), P t Bu2Me-HBF4 (0.005g, 0.2equiv) and Pd(OAc)2 (0.002g, 0.1equiv), and then use a syringe to draw 1,2,4,5-tetrafluorobenzene (0.015g, 1equiv) and solvent DMAc (2ml) into the reaction tube. After all the drugs and solvents are added, the device is evacuated and nitrogen-filled, and the process is repeated three times. The stopper is tightened under nitrogen. Finally, the device is transferred to an oil bath pot, the temperature is 140°C, and the reaction is terminated after condensation and reflux for 24h. After the reaction is cooled to room temperature, ethyl acetate / water is used for multiple extraction to remove the high-boiling solvent DMAc. The sample is mixed using a rotary evaporator, and a 25cm high chromatography column loaded with 100-200 mesh silica gel powder is used for separation and purification. The eluent with a polarity of [petroleum ether: dichloromethane = 10:1] is used for elution to obtain a white solid product with a yield of 85%. 1 HNMR (400MHz, CDCl3) δ7.87 (d, J = 7.9 Hz, 2H), 7.80 (d, J = 7.6 Hz, 2H), 7.46 (d, J = 8.1 Hz, 2H), 7.37 (t, J = 8.0 Hz, 2H), 7.23 (d,J=11.0Hz,4H), 7.16(d,J=7.5Hz,2H), 6.71(d,J=2.4Hz,4H), 6.37(dd,J=8.7,2.5Hz,4H), 6.32(s,2H), 6.30(s,2H); 13 C NMR (101MHz, CDCl3) δ158.0,154.8,154.5,151.1,139.6,137.6,128.7,127.9,127.5,1 26.7,126.6,126.1,124.6,119.2,118.9,115.1,110.0,100.7,76.3,76.0,75.7,67.1.

[0062] Example 5

[0063] m-type synthon m-shape

[0064]

[0065] All instruments needed for the reaction, including Schlenk reaction flasks and magnets, were cleaned in advance and placed in an oven for drying. First, the reaction flask was fixed on an iron stand and the device was wrapped with tin foil to ensure light protection. Then, the solid drugs DBrDSFX (0.100 g, 1 equiv), K2CO3 (0.048 g, 2 equiv), P t Bu2Me-HBF4 (0.005g, 0.2equiv) and Pd(OAc)2 (0.002g, 0.1equiv), and then use a syringe to draw 1,2,4,5-tetrafluorobenzene (0.015g, 1equiv) and solvent DMAc (3ml) into the reaction tube. After all the drugs and solvents are added, the device is evacuated and nitrogen-filled, and the process is repeated three times. The stopper is tightened under nitrogen. Finally, the device is transferred to an oil bath pot at 120°C, and the reaction is terminated after condensation and reflux for 48 hours. After the reaction is cooled to room temperature, ethyl acetate / water is used for multiple extractions to remove the high-boiling-point solvent DMAc. The sample was then mixed using a rotary evaporator, and separated and purified using a 30 cm high chromatography column loaded with 100-200 mesh silica gel powder. The product was eluted using an eluent with a polarity of [petroleum ether: dichloromethane = 10:1] to obtain a white solid product, which could be purified again by recrystallization using a dichloromethane / n-hexane mixed solvent, with a yield of 85%. 1 H NMR (400MHz, CDCl3) δ7.62 (q, J=7.6, 6.0Hz, 4H), 7.55 (d, J=7.6Hz, 4H), 7.18 (t, J=7.7Hz, 8H), 7.09–6.92(m,14H), 6.79–6.64(m,4H), 6.43(d,J=7.2Hz,2H), 6.38–6.16(m,8H), 5.45(s,2H); 13 C NMR (101MHz, CDCl3) δ157.3,154.2,151.6,150.4,149.2,136.6,135.9,128.8,126.3,126.0 ,125.6,124.8,123.3,119.6,119.0,118.7,117.6,114.2,109.2,102.5,100.0,66.2,51.7.

[0066] Application Example 1

[0067] Using the solution processing method, I-shape, U-shape, m-shape and G-DSFX were used as OLED light-emitting layers for device testing. The specific device structure is ITO transparent conductive substrate / PEDOT:PSS (40nm) / organic light-emitting layer (≈40nm) / TPBi (40nm) / LiF (1nm) / Al (100nm). The test results are as follows: Figure 4 and 5 :

[0068] according to Figure 4 The results show that: the turn-on voltage of I-shape is 3.9V. When the voltage reaches 8.9V, the current density is 71.13mA·cm-2, and the maximum brightness reaches 67.9cd·m-2; the turn-on voltage of U-shape is 6.9V. When the voltage is 10.9V, the current density is 97.37mA·cm-2, and the maximum brightness reaches 56.69cd·m-2; and the turn-on voltage of m-shape is 4.5V. When the voltage is 10.9V, the current density is 110.2mA·cm-2, and the maximum brightness reaches 45.43cd·m-2. Similarly, the turn-on voltage of G-DSFX is 6.4V. When the voltage is 9.4V, the current density is 38.13mA·cm-2, and the maximum brightness reaches 72.2cd·m-2.

[0069] Figure 4 b, 4d, 4f and 4h show the relationship between their corresponding CE and PE and the change of current density. It can be seen from the figure that the maximum current efficiency of I-shape is 0.12cd·A-1, and the maximum power efficiency is 0.06lm·W-1; the maximum current efficiency of U-shape is 0.08cd·A-1, and the maximum power efficiency is 0.3lm·W-1; the maximum current efficiency of m-shape is 0.05cd·A-1, and the maximum power efficiency is 0.01lm·W-1; and the maximum current efficiency of G-DSFX is 0.22cd·A-1, and the maximum power efficiency is 0.08lm·W-1.

[0070] according to Figure 5 The results show that the maximum emission wavelengths of I-shape, U-shape, m-shape and G-DSFX are at 432nm, 428nm, 436nm and 416nm respectively. Figure 4 bc corresponds to their EQE. It can be seen that the EQEmax of I-shape, U-shape, m-shape and G-DSFX are 0.08%, 0.06%, 0.03% and 0.15% respectively. It can be seen that in [spirofluorene oxygen heteroanthene-fluorophenyl]-based lattice aromatics, the lattice strategy can also improve the brightness and external quantum efficiency of the device.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A spirofluorene xanthracene-based lattice aromatic fluorescent material, the structural formula of the fluorescent material is as follows: in: It is a type of spirofluorene compound; Select any one of the following structures: Select any one of the following structures: Wherein X is any one of F, Cl, Br, I, CH3, NO2, and CH3O.

2. The spirofluorene xanthracene-based lattice aromatic hydrocarbon fluorescent material according to claim 1, wherein: The alkyl chain R is a straight chain type, including: a hydrogen atom, an alkane chain, an alkoxy chain, and an alkyl chain with a halogen atom of fluorine, chlorine or bromine introduced at the end. The specific structure is as follows: -H -C n H 2n+1 -OC n H 2n+1 -C n H 2n+1 F -C n H 2n+1 CI -C n H 2n+1 Br。 3. The spirofluorene xanthracene-based lattice aromatic hydrocarbon fluorescent material according to claim 1, wherein: The spirofluorene compound The specific structure is as follows:

4. A method for preparing the spirofluorene xanthracene-based lattice aromatic fluorescent material as claimed in any one of claims 1 to 3, which is synthesized by a CH bond activation lattice method, comprising: At a reaction temperature of 80-150°C, add U-shape synthon U-shape, dibromospirofluorene xanthene DBrDSFX base, ligand, organic solvent and palladium catalyst to react for 36-72 hours. The reaction concentration of the reaction system is 20mmol·L- 1 The molar ratio of the U-shape synthon U-shape and dibromospirofluorene oxygen anthracene DBrDSFX is 1:1, and finally the dibromospirofluorene oxygen anthracene-based lattice aromatic fluorescent material is obtained.

5. The preparation method according to claim 4, wherein: The base is selected from: potassium carbonate, potassium hydroxide, sodium carbonate, sodium bicarbonate, or a combination of two thereof; The ligand is selected from: PtBu2Me-HBF4, phosphoramidite ligand, 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, JosiPhos, or a combination of two thereof; The organic solvent is selected from: N,N-dimethylformamide, dimethyl sulfoxide, toluene, acetonitrile, or a combination of two thereof; The palladium catalyst is selected from the group consisting of: tetrakis(triphenylphosphine)palladium, palladium acetate, palladium pivalate, palladium trifluoroacetate, diphenylphosphinocenepalladium dichloride, dichlorobistriphenylphosphine palladium or palladium on carbon or a combination thereof.

6. The preparation method according to claim 5, wherein: The palladium catalyst is palladium acetate.

7. The preparation method according to claim 6, wherein: The amount of the palladium acetate substance is 0.025 to 0.05 times of the U-shape.

8. The preparation method according to claim 4, wherein: The reaction temperature is 120° C. and the reaction time is 48 h.

9. A spirofluorene xanthracene-based lattice aromatic fluorescent material prepared according to the preparation method of any one of claims 4 to 8.

10. Use of the spirofluorene xanthracene-based lattice aromatic fluorescent material according to claim 9 in an electroluminescent device, wherein: The electroluminescent device is an organic light emitting diode.

Citation Information

Patent Citations

  • Spirofluorene xanthene phosphine oxide electro-phosphorescent main materials and synthesis and application methods thereof

    CN102229623A

  • #-shaped grid spiro compounds and synthetic method thereof

    CN108276235A

  • Organic Electroluminescent Materials and Devices

    US20170186970A1